Ethnic differences and preference heterogeneity: assessing social pensions in Peru - Koen Decancq; Javier Olivera; Erik Schokkaert (Development Studies Research)
We examine the impact of the non-contributory social pension program (Pension 65) in Peru, highlighting its varying effects on the three main ethnic groups: Mestizo, Quechua, and Aymara. Notably, Aymara beneficiaries have experienced greater improvements in health outcomes compared to other Peruvians. To account for these ethnic differences when evaluating policy programs, it is essential to use a welfare criterion that reflects preference heterogeneity. We propose a natural criterion: a program benefits a recipient if it lifts them to a higher indifference curve. We contrast this approach with an alternative that uses self-reported subjective well-being to evaluate a policy program. Through a panel life satisfaction regression, we find evidence of preference heterogeneity between the Aymara and other ethnic groups, consistent with the observed differences. Lastly, we explore why, contrary to simple intuition, not all beneficiaries reach a higher indifference curve.